1999
DOI: 10.1034/j.1399-0039.1999.530311.x
|View full text |Cite
|
Sign up to set email alerts
|

CTLA4 polymorphisms in Spanish patients with rheumatoid arthritis

Abstract: Cytotoxic T-lymphocyte antigen 4 (CTLA4) polymorphisms located in the promotor region at positions -318 (C/T) and in exon 1 (49 A/ G) were investigated in 138 Spanish patients (37 men and 101 women) with rheumatoid arthritis and in 305 ethnically-matched healthy controls. When the allelic and genotypic frequencies corresponding to the CTLA4 -318 position were compared, no significant differences between patients and controls were found. However, when the CTLA4 49 A/G polymorphism was analysed, a significant in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
50
2
4

Year Published

2000
2000
2006
2006

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(57 citation statements)
references
References 19 publications
1
50
2
4
Order By: Relevance
“…Initial comparison showed an increased frequency of the +49 A/G*A allele in the RA group (data not shown). As the majority of studies reporting disease association with this SNP hint towards increased frequency of the G allele (Cai et al, 2005;Lee et al, 2003;Vaidya et al, 2002;Yanagawa et al, 2000;Matsushita et al, 1999;Gonzalez-Escribano et al, 1999;Seidl et al, 1998), we wondered whether the association seen in our study could be due to any idiosyncratic characteristics specific to this control population (168 healthy blood donors). Therefore, + 49 A/G distribution in a second, distinctive Northern Irish control population consisting of 307 Northern Irish 12 to 15-year-old school children was compared to that in Group 1.…”
Section: Resultsmentioning
confidence: 87%
See 1 more Smart Citation
“…Initial comparison showed an increased frequency of the +49 A/G*A allele in the RA group (data not shown). As the majority of studies reporting disease association with this SNP hint towards increased frequency of the G allele (Cai et al, 2005;Lee et al, 2003;Vaidya et al, 2002;Yanagawa et al, 2000;Matsushita et al, 1999;Gonzalez-Escribano et al, 1999;Seidl et al, 1998), we wondered whether the association seen in our study could be due to any idiosyncratic characteristics specific to this control population (168 healthy blood donors). Therefore, + 49 A/G distribution in a second, distinctive Northern Irish control population consisting of 307 Northern Irish 12 to 15-year-old school children was compared to that in Group 1.…”
Section: Resultsmentioning
confidence: 87%
“…The authors of the latter study also found the G allele of this SNP to be associated with lower mRNA levels of soluble CTLA-4 isoform, thus providing a rationale for a functional role in susceptibility to autoimmune diseases. Table 1 summarizes all the studies that have been done to date investigating the effects of CTLA-4 gene in RA (Cai et al, 2005;Lee et al, 2003;Rodríguez et al, 2002;Vaidya et al, 2002;Hadj Kacem et al, 2001;Yanagawa et al, 2000;Matsushita et al, 1999;Gonzalez-Escribano et al, 1999;Seidl et al, 1998;Orozco et al, 2004;Lee et al, 2002;Barton et al, 2000;Milicic et al, 2001). Results have been conflicting with some studies hinting towards association with RA, while others claiming to find no association at all.…”
Section: Introductionmentioning
confidence: 99%
“…4 Homozygosity for −318/T in the promoter of Ctla-4 is rarely present in a Caucasian population. [4][5][6][7] In our previous study, the frequencies of individuals with genotypes −318C/C, C/T, and T/T were 86%, 17% and 0%, respectively, in healthy individuals (n = 122) and 69%, 31%, 0%, respectively, in patients with Wegener's granulomatosis (n = 32). When we considered the prevalence of longer (AT)n in the 3Ј-untranslated region together with the promoter single nucleotide polymorphism (SNP), we found that all patients carrying the −318T allele were homozygous for (AT)n Ͼ86 bp alleles.…”
Section: Resultsmentioning
confidence: 99%
“…Recent research indicates that several of the non-HLA regions linked to Type I diabetes also show linkage to other autoimmune diseases, suggesting common pathogenic pathways shared by Type I diabetes and these other disorders [127,128]. For example, the IDDM3 region on chromosome 15q26 has been reported to be linked to coeliac disease [129,130], the IDDM6 region on chromosome 18q21 has been reported to be linked to Graves disease [131] as well as multiple sclerosis and rheumatoid arthritis [69], the IDDM8 region on chromosome 6q27 has been reported to be linked to rheumatoid arthritis [132], the IDDM12 (CTLA4) region on chromosome 2q33 has been reported to be linked to coeliac disease [133,134], Graves disease [78,135], multiple sclerosis [136] and rheumatoid arthritis [137,138], the IDDM16 region on chromosome 14q32 has been reported to be linked to multiple sclerosis [139], and the chromosome 1q42 region containing an unnamed diabetes locus has been reported to be linked to systemic lupus erythematosus [140,141] (for additional examples, see [128]). Although some of these co-localizations could be coincidental, the possibility remains that at least a few IDDM loci would be more accurately called autoimmunity susceptibility loci.…”
Section: Is Positional Candidate Mapping Feasible?mentioning
confidence: 99%